Hubungan Perilaku Picky Eating dengan Status Gizi Anak Prasekolah di PAUD Kiddy Kid Center Banda Aceh - Nidya Furi; Kiki Rezeki Amelia; Cut Rahmi Muharrina (Lembaga Pengembangan Kinerja Dosen, 2025)
Nutritional problems among preschool children remain a global and national concern. WHO (2017) reported that approximately 54% of child mortality under five is caused by malnutrition, while in Indonesia the prevalence of picky eaters reaches 20%, with West Java recording as high as 41.9%. The 2018 Basic Health Research (Riskesdas) data showed that the national stunting rate was still high at 30.8%, far from the national target of 19% in 2024. This study aimed to examine the relationship between picky eating behavior and physical activity with the nutritional status of preschool children at PAUD Kiddy Kid Center Banda Aceh. This was an analytical study with a cross-sectional design. The population included all 42 preschool children at the institution, selected through total sampling. Data analysis was carried out using univariate and bivariate (Chi-Square test) analyses. The results showed a significant relationship between picky eating behavior and nutritional status (p = 0.001), as well as between physical activity and nutritional status (p = 0.001). Conclusion: There is a significant association between picky eating behavior, physical activity, and the nutritional status of preschool children. It is recommended that schools and parents collaborate in promoting healthy eating patterns and encouraging physical activity from an early age.